Codex in Motion: Food Safety Standard Setting and Impacts on Developing Countries' Agricultural Exports - Christine Wieck; Jason H. Grant (EuroChoices, 2021)
The Codex Alimentarius, or `food code', was established to set international standards to ensure the safety and quality of food and agricultural products while at the same time creating a level playing field for international trade. However, less is known about the duration of the standards setting process in the Codex committees, and the extent to which trade is impacted when standards are delayed versus cases in which the adoption of standards was accelerated. This article reviews and evaluates three case studies in which Codex standards were rapidly adopted: Sulphur Dioxide (SO2) levels in cinnamon; melamine standards for milk and powder; and Codex guidance procedures in the case of melons. Two recent cases in which Codex standards have been held up are also considered: maximum levels of aflatoxins in ready-to-eat peanuts; and cadmium in chocolate. We find evidence that accelerated adoption of Codex standards is an important catalyst facilitating exports by some developing countries. Delays and non-adoption of Codex standards, on the other hand, can lead to significant export underperformance in certain countries and regions. Thus, Codex members would do well to reflect on the positive trade flow benefits that can be realised among developing countries who depend on international standards for export earnings.
Keywords: 630